2006
DOI: 10.1080/00140130600568451
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and patient safety: Observer-rated work stressors as predictors of characteristics of safety-related events reported by young nurses

Abstract: This study investigates the link between workplace stress and the 'non-singularity' of patient safety-related incidents in the hospital setting. Over a period of 2 working weeks 23 young nurses from 19 hospitals in Switzerland documented 314 daily stressful events using a self-observation method (pocket diaries); 62 events were related to patient safety. Familiarity of safety-related events and probability of recurrence, as indicators of non-singularity, were the dependent variables in multilevel regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 20 publications
2
78
0
6
Order By: Relevance
“…By demonstrating associations between nurse perceptions of chronic stress, daily hassles and safety perceptions, our findings support previous research reporting relationships between stress and error, and quality and safety issues within hospital nursing [e.g., 28,31,34]. However, much of the previous research which has examined associations between stress (and burnout) and patient safety, has adopted a between-person approach, so we know little about these relationships at the individual level.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…By demonstrating associations between nurse perceptions of chronic stress, daily hassles and safety perceptions, our findings support previous research reporting relationships between stress and error, and quality and safety issues within hospital nursing [e.g., 28,31,34]. However, much of the previous research which has examined associations between stress (and burnout) and patient safety, has adopted a between-person approach, so we know little about these relationships at the individual level.…”
Section: Discussionsupporting
confidence: 71%
“…Nonetheless, a small number of studies have utilised a within-person approach, for example, one such study found work stressors (e.g., time pressure) which were observer-rated, to predict safety-related event characteristics [34].…”
Section: Contribution Of the Researchmentioning
confidence: 99%
“…A stressful milieu in addition to enormous work pressures can also result in decreased patient safety (Carayon and Gurses, 2005). This has been confirmed in a study by Elfering et al (2006) that shows a direct correlation between stressful work situations and the safety of patients.…”
Section: Introductionsupporting
confidence: 60%
“…This type of working environment, which is demanding and which the nurses feel they have little control over, is perceived as stressful. A recent study has shown that minimal control over a work situation can increase the risk factors for patient safety (Elfering et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation